Inovasi Bahan Ajar Bahasa Jepang Pariwisata Untuk Meningkatkan Kemampuan Komunikasi Bahasa Jepang Mahasiswa Stp Trisakti Jakarta - Karnawati, Rita Agustina; Seruni, Ayu Putri (Jurnal Ilmiah Pariwisata, 2018)
Along with the progress of various fields of education, communication skills are the main goal in learning a language. One component of language skills that must be possessed is to speak, that is speaking well using correct grammar. To have these skills, an effort is needed from the language instructor so that it can facilitate the achievement of these objectives, thus students are expected to be able to communicate properly and correctly. To achieve these objectives the teacher needs teaching materials that can be a medium between instructors and learners to achieve learning goals.